(untitled) (Transport systems and technologies, 2020)
The article deals with the definition of rational approaches to carrying out traction calculations and the use of automated computer simulation. The basic values and calculation method for specific operating conditions have been established, which will allow to use economic resources rationally. The necessity of introducing analogue-digital devices under difficult economic conditions is proved. The mathematical model of traction calculations is offered. The necessity of using computer simulation tools is formed. Based on the proposed methods, you will be able to accurately determine train movement parameters, as well as improve accuracy and reduce time. Methods of mathematical modeling of the basic parameters of motion are offered that will allow to improve accuracy, reduce time and consumption of fuel and energy resources for train traction. The calculation part of the automated system is based on the developed methodology for determining the rational parameters of motion for specific operating conditions.